2010
DOI: 10.1016/j.ijgo.2010.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy‐related acute renal failure in eastern India

Abstract: Pregnancy-related acute renal failure is potentially fatal but largely preventable. Universal prenatal care and greater access to emergency obstetric services, especially in rural India, could avert PRARF and its consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 13 publications
10
39
1
Order By: Relevance
“…Moreover, Ashraf et al, [30] As regards the general characteristics of the studied sample, the mean age of patients was 28+6.9 years old this goes with the study of Arrayhani et al [31] who reported that the mean age was in an average of 29.03± 6.3 years old. Other studies backing up our findings regarding mean age are study of Khalil et al [32] which reported average age is 29 years old, However, the study done by Arora et al [33] found that the subjects' age appeared to be a factor significantly associated with unfavorable evolution (p-value <0.001). In the literature, this factor was associated with increase perinatal complications, including premature delivery.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Moreover, Ashraf et al, [30] As regards the general characteristics of the studied sample, the mean age of patients was 28+6.9 years old this goes with the study of Arrayhani et al [31] who reported that the mean age was in an average of 29.03± 6.3 years old. Other studies backing up our findings regarding mean age are study of Khalil et al [32] which reported average age is 29 years old, However, the study done by Arora et al [33] found that the subjects' age appeared to be a factor significantly associated with unfavorable evolution (p-value <0.001). In the literature, this factor was associated with increase perinatal complications, including premature delivery.…”
Section: Discussionsupporting
confidence: 64%
“…Our results revealed that postpartum hemorrhage represented the most significant relative risk factor associated with dialysis (14 women out of 34 had AKI). In this context, the percentage of patients who needed dialysis much less than ours in Hassan et al [44] it was (4%) Khalil et al [32] was (5%), Prakash et al [45] was (1%) and in Arora et al [33] was (3%) as well. The best results reported in various studies from developed world might be due to good literacy rate, better health care facilities and good antenatal and obstetrical care.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The incidence of PR-AKI is known to have decreased markedly in the past 50 years, from 20% to 40% in the 1960's to less than 10% in more recent years, primarily due to the legalization of abortion and improvements in antenatal care (8). Statistics from developing countries show that the incidence of PR-AKI in India, Africa and Pakistan to be 7-11%, 57% and 18%, respectively (5,8,(15)(16)(17)(18). Epidemiological data for PR-AKI in other countries are shown in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed in 28% cases in study by Ansari et al and 5% of cases in study by Arora et al 9,10 Total recovery was obtained in 84% of the cases, whereas Arora et al, Goplani et al, and Erdemoglu et al reported a total recovery of renal function in 42%, 54.3%, and 61%, respectively. 10,13,14 Hence, there is a need for education and improvement in ante-and postnatal care, especially in the rural areas, and the practice of illegal abortions by untrained personnel has to be stopped. The mortality related to PRAKI has declined to less than 10% in Europe and North America, while the reported mortality rate of PRAKI has decreased from 56% in 1987 to 24.39% in 2005 in India.…”
mentioning
confidence: 91%